Personal Branding Politikus Melalui Media Sosial - Dyah Mentari Putri; Guntur Freddy Prisanto; Niken Febrina Ernungtyas; Sekartaji Anisa Putri (Jayapangus Press, 2022)
Self-branding as a display for politicians is important. However, it is rarely found that the display is just a display. The eight laws of personal branding can help us dissect how politicians look from their performance and qualities in the real world. In the world of communication that has been visited by social media and digital technology, media literacy is important. How political actors carry out personal branding through social media we need to know and dig deeper. Through this research, there is an objective to explore how political actor Edhie Baskoro Yudhoyono (EBY) carries out personal branding through social media. And aims to find out how followers perceive the value of personal branding that is carried. The research method used in this research is descriptive qualitative. It was carried out by conducting in-depth interviews with five informants. Two informants are part of the EBY winning team. The other three informants are followers of EBY's social media account. The findings from the interview were explored through three stages of qualitative coding. These are open coding, axial coding, and selective coding. The results and conclusions from the research data found that EBY's personal branding fulfills eight personal branding laws. These are the law of specialization, the law of leadership, the law of personality, the law of distinctiveness, the law of visibility, the law of unity, the law of persistence, and the law of goodwill. Regarding followers' perceptions of the value of EBY's personal branding, each follower perceives according to their own views and interests. However, the personal branding value perceived by followers is in accordance with the values ​​constructed by EBY and the team.